A new species of Triepeolus (Hymenoptera: Apidae), with comments on T. utahensis (Cockerell) and T. melanarius Rightmyer - Rightmyer, Molly G.; Kono, Yoshiaki; Kohn, Joshua R.; Hung, Keng-Lou James (Zootaxa, 2014)
Triepeolus matildae Rightmyer, sp. nov., from Mexico (Baja California) and USA (California) is described and both genders are differentiated from the closely related species T. utahensis (Cockerell) using morphological characters. The synonymy of T. utahensis and T. heterurus was established in Rightmyer (2008); however, the younger name was used in that treatment, an error that is corrected herein. Males of both T. matildae and T. utahensis are additionally differentiated from T. melanarius Rightmyer, which is morphologically similar in that gender only. DNA barcoding evidence supporting the recognition of the new species is additionally presented.